Determination of optimal conditions for laccase production by Pleurotus ostreatus using sawdust as solid medium and its use in phenol degradation (Baghdad Science Journal, 2012)
The ability of four local fungal isolates for extracellular laccase production has been tested with five grams 1:1(w/v) humidified sawdust as substrate in mineral salt medium. After 21 day of incubation at 25±1 ? C and using one mycelial plug (5mm), higher level of laccase activity (0.15U/ml) and specific activity (15U/mg) were observed by Pleurotus ostreatus in comparison with other fungal isolates. The results of optimum conditions for laccase production from selected isolate showed that, the maximum laccase activity (0.55U/ml) and specific activity (55U/mg) were obtained at moisture ratio 1:3 (w/v), using 3 mycelial plugs (5 mm), after 15 days incubation period at 25±1 ? C. The results of phenol degradation by crud laccase revealed that, 100% degradation of phenol occurred after 24 hr of incubation at 25 ? C using shaking water bath except at 200mg/l, the remaining phenol was 10.13%.